Genes and genetics belong to maize haploid induction - Khammona, Kanogporn; Dermail, Abil; Chen, Yu-Ru; Lübberstedt, Thomas; Wanchana, Samart; Toojinda, Theerayut; Arikit, Siwaret; Ruanjaichon, Vinitchan (Frontiers in Plant Science, 2025)
Maize (Zea mays L.) is a globally significant cereal crop with diverse food, feed, and industry uses. The rapid development of homozygous inbred lines via double haploid (DH) technology has revolutionized maize breeding, reducing the time and cost required for cultivar improvement. This review synthesizes advances in haploid induction systems, focusing on the genetic mechanisms underlying both paternal and maternal inducers. Key genes such as IG1, MTL/ZmPLA1/NLD, ZmDMP, ZmPLD3, ZmPOD65, and the centromeric histone variant CENH3 are examined for their roles in haploid embryo formation. Methods of haploid identification based on DNA content and phenotypic markers (e.g., R1-navajo and Pl1 genes) are critically assessed, including recent innovations that enhance selection accuracy. Additionally, the integration of kernel oil content (KOC) as a quantitative trait for haploid discrimination is discussed. Progress in artificial and spontaneous chromosome doubling techniques, particularly the roles of colchicine, N2O treatments, and identified QTL governing spontaneous haploid genome doubling (SHGD), are highlighted. This review underscores the transformative potential of combining novel genetic tools, precision phenotyping, and genome-editing strategies to further optimize DH technology for maize improvement, ultimately facilitating next-generation plant breeding programs.